2015
DOI: 10.1002/ajp.22440
|View full text |Cite
|
Sign up to set email alerts
|

Need for speed: Sexual maturation precedes social maturation in gray mouse lemurs

Abstract: The life history of mammals underlies a fast-slow continuum, ranging from "slow" species with large body size, delayed sexual maturation, low fertility, and long lifespan, to "fast" species showing the opposite traits. Primates fall into the "slow" category, considering their relatively low offspring numbers and delayed juvenile development. However, social and sexual maturation processes do not necessarily have to be completed simultaneously. The comparison of the timeframes for sexual and social maturation i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
11
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
1
1

Relationship

3
5

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 52 publications
0
11
0
Order By: Relevance
“…In addition, although several studies reported mouse lemurs’ poaching (Gardner & Davies, 2014; Jenkins et al, 2011) and its negative effects on DF use (Figure 3, Table 1), it seems not be as frequent as for larger-bodied lemur species (Jenkins et al, 2011; Lehman & Ratsimbazafy, 2001). Mouse lemur populations are likely to be less susceptible to poaching than larger-bodied lemurs because of their shorter generation time and higher reproductive rate (Hohenbrink, Zimmermann, & Radespiel, 2015; Zimmermann & Radespiel, 2013). Therefore, mouse lemur harvesting needs to be formally evaluated to determine under which conditions sustainability can be achieved (Gardner & Davies, 2014; Golden, 2009).…”
Section: Discussionmentioning
confidence: 99%
“…In addition, although several studies reported mouse lemurs’ poaching (Gardner & Davies, 2014; Jenkins et al, 2011) and its negative effects on DF use (Figure 3, Table 1), it seems not be as frequent as for larger-bodied lemur species (Jenkins et al, 2011; Lehman & Ratsimbazafy, 2001). Mouse lemur populations are likely to be less susceptible to poaching than larger-bodied lemurs because of their shorter generation time and higher reproductive rate (Hohenbrink, Zimmermann, & Radespiel, 2015; Zimmermann & Radespiel, 2013). Therefore, mouse lemur harvesting needs to be formally evaluated to determine under which conditions sustainability can be achieved (Gardner & Davies, 2014; Golden, 2009).…”
Section: Discussionmentioning
confidence: 99%
“…It is known from the gray mouse lemur ( M. murinus ) that males can compete severely for the access to estrous females under natural conditions ( M. murinus , [15]) and in captivity ( M. murinus , [67]), and that conflict rates among the sexes are higher and female dominance is more expressed in the reproductive season than in the non-reproductive season, at least in captivity ( M. murinus , M. lehilahytsara , [42]). It was therefore predicted that social tolerance (i.e.…”
Section: Discussionmentioning
confidence: 99%
“…Not much is known about the social relationships in these dispersed social networks from the wild, although occasional nocturnal affiliative and agonistic encounters have been observed in several species [20, 29, 31, 3739]. However, recent work from captivity suggests that female dominance that is untypical for mammals but formerly thought to be typical for most lemur species [40, 41], may be much more variable and plastic in mouse lemurs than expected [24, 25, 42]. For example, conflict rates, the probability for females to win conflicts, and the proportion of females being dominant over males varied between species ( M. murinus , M. lehilahytsara ) and season (reproductive vs. non-reproductive) and furthermore depended on age and breeding experience [25, 42].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Mouse lemurs possess a functional vomeronasal organ (VNO 22 23 ) and have a repertoire of over 200 vomeronasal receptor genes 24 25 that are expressed in the VNO but also partially in the main olfactory epithelium 22 . Olfaction may be involved in various contexts of intraspecific communication, as in marking group ownership of sleeping sites 19 , or in many aspects of reproduction, and may be used within and between the sexes 20 26 27 28 29 .…”
mentioning
confidence: 99%